History, imagination and the performance of music - Walls, Peter (Rochester Boydell & Brewer, 2003)
The legitimacy of applying historical research to musical performance has been much argued about in recent years. Those advocating historical authenticity have been attacked on philosophical, aesthetic, and even practical grounds. This book both defends the practical value of trying to determine how music sounded in the past and develops an intellectual and musical justification for relating historical research to performance. From the outset Peter Walls stresses the need for research driven by curiosity rather than by the desire to justify a particular approach. Arguing that a performance determined entirely by historical rules is an impossibility, he asserts that the imagination is inevitably involved. His book envisages a relationship between historical knowledge and imagination that is dynamic and stimulating. Case studies range from printing formats and performance in seventeenth-century violin music, to tracking composer intention through the rehearsal and production phases of nineteenth and twentieth century operas. PETER WALLS is professor of music at Victoria University of Wellington, and chief executive of the New Zealand Symphony Orchestra.